Patients with Primary Sjögren's Syndrome Who Are Positive for Autoantibodies to Tripartite Motif-Containing Protein 38 Show Greater Disease Severity (2016)
Objective Autoantibodies reactive with Ro52 (tripartite motif-containing protein 21 [TRIM21]) are detected in 70% of patients with primary Sjögren's syndrome (SS). TRIM21 belongs to a 34-member C-IV family of TRIM proteins. Although autoantibodies against other TRIM proteins within the C-IV family have been detected in the sera of patients with primary SS, their clinical relevance remains unclear. This study was undertaken to investigate the frequency of anti-TRIM38 in patients with primary SS and evaluate its association with various clinical measures of the disease. Methods Serum samples from patients with primary SS (n = 235) and controls (n = 50) were analyzed for reactivity with in vitro-transcribed and -translated 35S-methionine-labeled TRIM38 protein. The associations of anti-TRIM38 with various laboratory and clinical measures of primary SS were evaluated. Reactivity of anti-TRIM38 with different structural domains of TRIM38 was analyzed. Affinity-purified anti-TRIM38 antibodies were used to immunoprecipitate TRIM21. Results TRIM38-reactive autoantibodies were detected in the sera of 24 of the 235 patients with primary SS and 2 of the 50 controls. Anti-TRIM38 positivity was significantly associated with the presence of anti-Ro60, anti-Ro52, anti-La, rheumatoid factor, and hypergammaglobulinemia. Clinically, anti-TRIM38 was associated with significantly higher ocular surface staining scores, lower Schirmer's test scores, and minor labial salivary gland biopsy focus scores of ?3.0. Anti-TRIM38 antibodies mainly recognized the cortactin-binding protein 2 (CortBP-2; amino acids 128-238) and the B30.2/SPRY (amino acids 268-465) domains on TRIM38. Affinity-purified antibodies to TRIM38-CortBP-2 and TRIM38-B30.2/SPRY domains reacted with TRIM21. Conclusion Our data demonstrate that anti-TRIM38 specificity arising in a subset of patients with primary SS is associated with increased severity of the disease. © 2016, American College of Rheumatology.